Discussion On Mechanization Technology of Sugarcane Production in Guangxi - Liu, Haitao; Jinlin Yang (International Journal of Management and Education in Human Development, 2022)
Sugarcane is one of the main cash crops planted by farmers in Guangxi, The output is larger in Guangxi, and It is one of the main economic incomes of farmers in Guangxi. Sugarcane mechanization technology is used for production, Can save a lot of manpower and labor, increase efficiency, And the yield of sugarcane can be improved, Achieving the purpose of increasing revenue. This paper mainly introduces that sugarcane mechanized production is of great significance to farmers, and gives some suggestions to improve sugarcane production efficiency and promote the development of sugarcane mechanized technology, which can provide a reference for related scientific research on sugarcane machinery.